Colonisation of lettuce by Listeria Monocytogenes. (25th July 2018) - Kyere, Emmanuel O.; Palmer, Jon; Wargent, Jason J.; Fletcher, Graham C.; Flint, Steve
Abstract: Foodborne illnesses involving ready‐to‐eat vegetables are increasing. Lettuce is the third most consumed fresh vegetable in the United States with worth approximately 1.9 billion, making it the most valuable leafy crop. Previous reviews have described the survival of pathogenic bacteria such as E . coli O157:H7 and Salmonella on different ready‐to‐eat vegetables, but the colonisation of lettuce by Listeria has received limited attention. Listeria monocytogenes has high mortality compared to other foodborne pathogens such as Salmonella . This review summarises recent studies on the mechanisms of attachment and colonisation of Listeria on lettuce leaves. We discuss various factors that affect colonisation of lettuce by Listeria in terms of the number of bacteria that can be recovered after inoculation, the effect of washing, different radiation treatments and cultivation systems on the recovery of Listeria . We propose strategies that can be used to minimise the colonisation of lettuce by Listeria to enhance food safety. Abstract : Upper surface of lettuce leaf colonised by Listeria monocytogenes under a Scanning Electron Microscope. A = Listeria monocytogenes . B = Lettuce leaf surface.